LEGAL PROTECTION OF THE PARTIES IN LAND PURCHASE TRANSACTIONS THROUGH UNDERHAND AGREEMENTS - Dewi Arnita Sari (Jurnal Al-Dustur, 2022)
This study aims to (1) determine legal protection for parties in the practice of buying and selling land without involving PPAT (2) To determine the factors that influence the community not to involve PPAT in land buying and selling activities in Tomilito District, North Gorontalo District. This research is an empirical research, the type of empirical approach is used to study or analyze primary data in the form of field data where the research is conducted, the results of direct interviews are then linked to secondary data in the form of book materials.The results of this study indicate that legal protection for the parties in the sale and purchase of land in Tomilito sub-district is divided into two types, namely preventive protection and repressive, namely the availability of legal rules that guarantee the creation of a buying and selling process that has perfect evidentiary power, whereas in the event of a dispute, the availability of a dispute resolution mechanism. Apart from that there are also factors that affect the community so that not involving PPAT in the sale and purchase of land in Tomilito sub-district in general is related, a long process, drains energy and costs a lot.The recommendation of this research is that it is suggested to increase the cooperation of each related agency and the integration of existing legal instruments, especially those related to land, both by the central and regional governments.